Relações comparativas entre características de contexto e o Índice de Desenvolvimento da Educação Básica (IDEB) em municípios de pequeno porte do estado do Paraná - Elsenbach, Loreci Aparecida Wickert (2022)
The quality of education theme has been the subject of debates in public policies, mainly since the 1990s. With the creation of the Basic Education Development Index (IDEB) in 2007, these policies are treated with greater emphasis, as this index is considered the main instrument to “measure” the “Brazilian basic education quality”. However, the IDEB has received criticism and disagreements when treated as the only and main indicator of teaching quality, resulting from only two dimensions: performance and school flow. Large-scale evaluations are public policies that claim to attest to "education quality", but we understand this term as something comprehensive, complex, and challenging, involving internal and external aspects of the school context, which are often neglected and not computed in evaluation processes. This study aimed to identify relationships between context characteristics and school performance measured by IDEB in small municipalities in the state of Paraná. The municipality of Serranópolis do Iguaçu, parameter in this research, was selected for having stood out with expressive scores in consecutive editions of IDEB. This study involved 61 small municipalities of Paraná, through the selection of comparability criteria. The studies depart from a comparative perspective, considering the different contexts and specificities of the surveyed municipalities. In the comparative analyzes, socioeconomic indicators (Gini Index and Poverty Incidence Index), and educational indicators (Illiteracy Rate and Age-Grade Distortion) were used, which were related to the IDEB, aiming to understand existing variables that determine or influence school performance and consequently the IDEB results in small municipalities. We consider that studies developed with this theme may contribute with reflections and analyses, helping managers and others involved in educational aspects to better understand the concept of the term "quality of education", to recognize the factors that affect the results of large-scale external evaluations, measured by IDEB, and rethink the need to implement policies aimed at reducing social and educational inequalities